Non-performing loans' impact on bank efficiency: An empirical analysis on Chinese state-owned banks - Ning Xingyu (2022)
This research investigates the impact of non-performing loans on bank efficiency in Chinese state-owned banking sector. The results indicate a negative effect of non-performing loans on bank efficiency in Chinese State-owned banks throughout 2011Q1 - 2021Q3. We take seasonal revenue as the indicator of bank efficiency in our baseline models and seasonal profit denoting bank inefficiency in our robustness test. The findings of our study highlight non-performing loans are an important indicator of bank inefficiency in Chinese SOBs (State-owned banks). We applied Prais-Winsten regression to our panel data, which is a special case of Feasible Generalized Least Squares (FGLS), to correct the serial correlation and cross-sectional correlation of our fixed effect model. The novelty of our paper also lies in the application of FGLS to the study of non-performing loans. Overall, the implication of our research is in line with the extant literature that policy makers should consider reducing non-performing loans in the post-crisis era to improve the efficiency in banks.